Building for tomorrow: Analyzing ideal thermal transmittances in the face of climate change in Brazil - Rodrigues, Eugénio (2024)
The climate will become hotter, and buildings will perform differently as outdoor conditions evolve. If the lowest energy demand is desired, it is crucial to determine the ideal thermophysical properties of the envelope over the buildings' life span. However, the scientific literature is still scarce in providing a compelling answer. Therefore, this study (i) determines ideal thermal transmittance values (U-values) for present-day and future climates, (ii) determines to what extent the thermophysical properties will need to change to remain ideal, (iii) identifies different trends of U-values over time, (iv) establishes a relationship between outdoor air temperatures, cooling and heating setpoints, and ideal U-values, and (v) proposes a set of design strategies according to each trend. The EPSAP generative design method was used to create a large dataset of residential buildings with random geometries and U-values to evaluate their energy demand for heating and cooling in EnergyPlus. The thermal performance of each building was evaluated for 30 locations in Brazil for the current period and two future timeframes (2050 and 2080). The Future Weather Generator tool was used to morph today's typical meteorological weather to match the EC-Earth3 data for the SSP5–8.5 scenario. Although climate change has a similar relative impact, its consequences differ over time in each location. The ideal U-values have different trends in different regions: (a) remaining unchanged in the future, (b) changing from being the highest possible to the lowest of the analyzed range in 2050 or 2080, and (c) being mid-range values in the present and with similar or lower values in the future climate. The impact on the thermal loads of maintaining the present-day ideal U-values also varies significantly in the future timeframes, from being nil to representing an increase reaching 30 % in 2050 (Δ 2.94 MW⋅h ± 0.06 MW⋅h) and 57 % in 2080 (Δ 6.05 MW⋅h ± 0.09 MW⋅h). Therefore, building design professionals need to use different strategies according to each region and consider how climate evolves during the lifetime of the building.